What influence do the Sri Lankan Folk theatre and Dance traditions have on Sri Lankan society? - Sanjeewa, Winojith (Technium Social Sciences Journal, 2021)
Mahavamsa , the most widely cited historical Pali chronicle, records information about the performing arts of the Yaksha and Naga tribes who lived even before the advent of Vijaya to Sri Lanka in 543 BC. With the introduction of Buddhism and Hinduism to Sri Lanka (250 BC), ritual and religious based ceremonies inspired by India developed and the performing artiste played a significant role in those ceremonies. Because of the subjugation of Sri Lanka to Portuguese rule in 1505, the Dutch in 1658 and the British in 1815 several changes took place in Sri Lankan art. With the Sinhalese-Buddhist policy declared in 1956, the main ethnic groups of Sinhalese and Tamil separated into two distinct groups with the result that a civil war lasting more than twenty-five years ensued. Along with this, the performing arts divorced itself from the common ethnic background and separated into two as Sinhalese and Tamil. This directly impacted on the arts with the changes in the social, cultural, political and economic fields allied to the agrarian economy that occurred under each period of colonisation. This paper will analyse and discuss how some of the Sri Lankan Folk theatre and Dance traditions and artiste have overcome issues such as caste, ethnicity and gender in their practice and how, in overcoming such obstacles, this can contribute to an improvement in ethno-religious cohesion in wider society.